2017
DOI: 10.1108/ijmpb-03-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Factor analyzing project management practices in the United Arab Emirates

Abstract: Purpose The purpose of this paper is to examine the underlying dimensional structure of project management practices to identify key factors that underpin the successful completion of projects. Design/methodology/approach It employs exploratory factor analyses to investigate the interrelationships of the survey items synthesized from the literature by retaining and reorganizing the important information from the original data while redundant information is removed. Findings The nine theoretical constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Research has demonstrated that project successsuccessful completion of the final product for which the project was initiated is a key factor in achieving a competitive advantage in terms of performance and output (Baccarini, 1999). Given the importance of project success in anticipating successful work outcomes, previous studies have examined its role in terms of political stability (Kwak, 2002), flexible project planning (Khan et al, 2000), satisfaction of stakeholder groups (Albert et al, 2017) and connection of project management practices with project outcomes (Ajmal et al, 2017). However, limited studies have examined the role of psychological abilities, specifically employees' psychological empowerment, that may potentially interact with project success (Rowlinson & Cheung, 2008) in project-based organisations (Sok et al, 2018), particularly the combination of mediating and moderating mechanisms in the aforementioned relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that project successsuccessful completion of the final product for which the project was initiated is a key factor in achieving a competitive advantage in terms of performance and output (Baccarini, 1999). Given the importance of project success in anticipating successful work outcomes, previous studies have examined its role in terms of political stability (Kwak, 2002), flexible project planning (Khan et al, 2000), satisfaction of stakeholder groups (Albert et al, 2017) and connection of project management practices with project outcomes (Ajmal et al, 2017). However, limited studies have examined the role of psychological abilities, specifically employees' psychological empowerment, that may potentially interact with project success (Rowlinson & Cheung, 2008) in project-based organisations (Sok et al, 2018), particularly the combination of mediating and moderating mechanisms in the aforementioned relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the latest technology as a system for team needs in daily work [8], [9], [16], [17], [11], [16], [17] Leadership The ability of leaders to influence their members to achieve goals [18], [8], [19], [20], [10], [21], [2], [14], [22], [23], [24] Management Support Full support and commitment from top management to help the team [18], [25], [2], [11], [26], [13] Creativity, Innovation, and Improvement…”
Section: Key Indicators Definition Referencesmentioning
confidence: 99%
“…Encourage innovative thinking that can contribute to improving contribution for teams [27], [11], [26], [28], [29], [15], [23] Trust and Respect All members need to trust each other and be treated equally [16], [11], [26], [28], [29] Encouraging Initiative Motivate all team members to come up with a good and doable idea that can make a positive contribution to the team [8], [19], [11], [26], [29], [22], [30] Teamwork Responsive to changes and uncertainties well during the project [16], [11], [26], [12], [13], [14], [29], [10] Security Ensure the health and safety of members working there (Physiological and psychological safety) [16], [18], [19], [11], [30] Information Sharing Information should be accessible and available to all team members [7], [11], [26], [12], [31], [29], [22], [23] Close Monitoring Ability to record all existing activities, compare with targets and analyze errors and take corrective action [32], [19], [26],…”
Section: Key Indicators Definition Referencesmentioning
confidence: 99%
“…In a recent study, AlShamsi and Ajmal (2018b) affirm that organizational leadership and culture are the most significant factors impacting knowledge sharing. As such, an organization relies entirely on its human capital to learn and share knowledge in order to add value for future projects (Ajmal et al , 2017; Mainga, 2017; Sense, 2008).…”
Section: Introductionmentioning
confidence: 99%